Affect, Semiotics, Volition: Heteroregulation and Affectivating. - Larocco, Steve (I Activate You To Affect Me, 2018)
The second volume of Annals of Cultural Psychology is dedicated to the affective nature of human social relationships with the environment. The chapters here included explore the historical, theoretical and practical dimensions of the concept of affectivating originally introduced by one of us (Valsiner, 1999), as a potential tool of inquiry into the affective-sensitive dimension of psychological life within a cultural-psychological framework. The concept of affectivating involves two psychological dimensions often undervalued or even obliterated from contemporary cultural psychology, namely the affective involvement and the agentivity of people in their social encounters. Through several examples –‘feeling-at-home’, silence spaces and rituals, memorials, music and poetry, among others– we show individual’s concrete actions in mundane everyday life aim to give an affective personal sense to the world around. This focuses on the primary affective nature of human meaning construction that guides the person in one’s continuing feeling-into-the-world. At a theoretical level the notion of affectivation challenges contemporary Cultural Psychology to rescue subjectivity, not only symbolism. Affectivation propounds a return to the long, but partially forgotten, organismic tradition, represented in the history by thinkers like Wilhelm Dilthey, Jakob von Uexküll and Kurt Goldstein. Cultural psychology has to bring semiosis back to the vital background of human experience.

Normal: A Chaplain, a Community with HIV/AIDS, and the Eternal Life of Stories - Kerr, Audrey Elisa (Cascade Books, 2018)
This book chronicles the intersection of chaplaincy, autopathography (illness narratives), and stigmatized illness through the observations and stories of a chaplain working at a facility for people with HIV and AIDS. Trained as both an ethnographer and a chaplain, Audrey Elisa Kerr uses memoir to bridge the relationship between caregiver and patient, and allows stories of marginality to frame both her patients’ stories and her own.
Keywords: dept.eng

The Number 43: The Life and Legacy of Wild Bill Greco - Greco, Sarah (Coastal 181, 2018)
Keywords: Stock car racing; United States; United States; Stock car drivers; dept.eng

After Hours: Poems - Mottola, Pat (Five Oaks Press, 2018)
Keywords: dept.eng

The Other, Shame, and Politics: Levinas, Justice, and Feeling Responsible - Larocco, Steve (Religions, 2018)
Adi Ophir has suggested that the political realm is an order of evils, producing and managing regular forms of suffering and violence rather than eliminating them. Thus, the political is always to some extent a corrupted order of justice. Emmanuel Levinas’ work presents in its focus on the face-to-face relationship a means of rethinking how to make the political more open to compassionate justice. Though Levinas himself doesn’t sufficiently take on this question, I argue that his work facilitates a way of thinking about commiserative shame that provides a means to connect the face-to-face to its potential effects in the political sphere. If such shame isn’t ignored or bypassed, it produces an unsettling relation to the other that in its adversity motivates a kind of responsibility and care for the other that can alter the public sphere.
2 citations (Crossref) [2023-10-31]
Keywords: Commiseration; Evil; Guilt; Law; Levinas; Other; Politics; Responsibility; Shame; Sympathy; commiseration; dept.eng; evil; guilt; law; other; peer-reviewed; politics; responsibility; shame; sympathy

Teaching race, gender, and narrative form in Gertrude Stein’s “Melanctha.’ - Blackmer, Corinne E. (Approaches to Teaching the Works of Gertrude Stein, 2018)
A trailblazing modernist, Gertrude Stein studied psychology at Radcliffe with William James and went on to train as a medical doctor before coming out as a lesbian and moving to Paris, where she collected contemporary art and wrote poetry, novels, and libretti. Known as a writers writer, she has influenced every generation of American writers since her death in 1946 and remains avant-garde.Part 1 of this volume, Materials, provides information and resources that will help teachers and students begin and pursue their study of Stein. The essays of part 2, Approaches, introduce major topics to be covered in the classroomrace, gender, feminism, sexuality, narrative form, identity, and Steins experimentation with genrein a wide range of contexts, including literary analysis, art history, first-year composition, and cultural studies.
Keywords: dept.eng

The divine sublime: Educating spiritual teachers in Emerson’s divinity school address - Blackmer, Corinne E. (Approaches to Teaching the Works of Ralph Waldo Emerson, 2018)
A leader of the transcendentalist movement and one of the country's first public intellectuals, Ralph Waldo Emerson has been a long-standing presence in American literature courses. Today he is remembered for his essays, but in the nineteenth century he was also known as a poet and orator who engaged with issues such as religion, nature, education, and abolition.This volume presents strategies for placing Emerson in the context of his time, for illuminating his rhetorical techniques, and for tracing his influence into the present day and around the world. Part 1, "Materials," offers guidance for selecting classroom editions and information on Emerson's life, contexts, and reception. Part 2, "Approaches," provides suggestions for teaching Emerson's works in a variety of courses, not only literature but also creative writing, religion, digital humanities, media studies, and environmental studies. The essays in this section address Emerson's most frequently anthologized works, such as Nature and "Self-Reliance," along with other texts including sermons, lectures, journals, and poems.
Google-Books-ID: qseCDwAAQBAJ
Keywords: Language Arts & Disciplines / Study & Teaching; Literary Criticism / American / General; Literary Criticism / Modern / 19th Century; dept.eng

Reading curriculum in the age of spectacle: Reclaiming experience and dialogue in reading - Sinclair, Meredith N. (Journal of Curriculum Theorizing, 2018)
Using Fahrenheit 451 as a model for reading in the age of spectacle, this paper offers a critique of reading curriculum driven by Common Core State Standards for English Language Arts and Literacy in History/Social Studies, Science, and Technical Subjects (CCSS-ELA), which divorces reading from dialogue and lived experience. Drawing on Debord’s (1967/1983) notion of spectacle, the author considers how our current cultural moment may be shaping and shaped by an alienated and alienating curriculum of reading. By embracing the political implications of reading curriculum, we can reclaim reading as a dialogic activity grounded in the world.
Citation Key Alias: lens.org/181-243-807-539-577, pop00288 tex.type: [object Object]
Keywords: dept.eng; literacy; peer-reviewed; reading; ⛔ No DOI found

Fluid boundaries in 'The Awntyrs off Arthure' and 'Sir Isumbras' - Richmond, Andrew (Open Library of Humanities, 2018)
Encounters with water shape the Middle English romances of The Awntyrs off Arthure and Sir Isumbras. In the latter, rivers and the 'Greek Sea' serve to distinguish separate sections of the narrative: the river marks the point at which the titular hero's family unit begins to break down, while the beach of the sea marks the lowest point of his social power. Yet his later traversal of the Greek Sea itself allows him to reassemble his family and reclaim his aristocratic power. In Awntyrs, the Tarn Wathelene (or Wadling) ties the actions of the romance's first episode onto a specific spot in the real-world English landscape, while connecting the text to a number of other Arthurian romances that also mention or take place near the tarn. This article, then, argues that the waterscapes in these two texts illustrate a late-medieval understanding of tarns, rivers, and seas as explicitly alien, yet intimately physical embodiments of divine power in the natural world. Taken together, these poems-one a metrical romance, the other alliterative-show how interests in waterscapes crossed boundaries within the muddy genre of romance itself, and reveal that water upsets such human categories as family and property. Tarns, rivers, and seas turn human bodies, instead, into their possessions; the disturbing experience of that dehumanizing process should, these texts imply, wear the world, its history, and its bonds away, until even the greatest knights or ladies are left alone with watery forms beyond the pale of human understanding. © 2018 The Author(s).
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/049-894-901-510-053, pop00161
Keywords: dept.eng; peer-reviewed

The Rise of Silas Lapham: Authoritative Text, Contexts, Criticism - Howells, William Dean (W.W. Norton & Company, Inc., 2018)
Keywords: Fiction; Fiction; Domestic fiction; Psychological fiction; Boston (Mass.); Fiction; Rich people; Fiction; Socialites; Howells; William Dean; 1837-1920. Rise of Silas Lapham; Businessmen; dept.eng

Science and technology in Hawthorne’s short fiction - Ellis, Scott (Nathaniel Hawthorne in the College Classroom: Contexts, Materials, and Approaches, 2018)
This new work is currently the only book devoted to the teaching of one of the most canonical and frequently taught American authors.In addition to a Preface by the noted Hawthorne scholar Larry J. Reynolds [University Distinguished Professor and Thomas Franklin Mayo Professor of Liberal Arts Department of English Texas A&M University] the contributors include well-known and rising teacher-scholars who offer theoretical and pedagogical approaches to Hawthorne's four published novels and a wide range of his short stories.The specially commissioned essays are designed to help teachers meet students at points of genuine interest and need. They incorporate biographical, literary, historical, and multidisciplinary scholarship. The studies are further grounded in specific contexts such as literature surveys, interdisciplinary humanities courses, upper division literature seminars, and study abroad courses.Special emphasis is given to the issues of gender, science, and visual culture (including film adaptations). Offering both theoretical and practical classroom resources, this anthology confirms the continued vitality of Hawthorne's work - his critiques of religious and moral authority are more relevant than ever in today's global political environment - even as it showcases how today's "Hawthorne" is more of a diverse amalgam of texts and perspectives than ever before. Given its diversity of approaches and authors (including essayists from Germany, Israel, and Sweden), Nathaniel Hawthorne in the College Classroom charts new paths for reading and teaching Hawthorne in the 21st century.
Keywords: dept.eng

Reaping something new: African American transformations of Victorian literature. - Baraw, Charles (Journal of British Studies, 2018)
0 citations (Crossref) [2023-10-31] Citation Key Alias: barawDanielHackReaping2018 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: dept.eng; peer-reviewed

States of the Union - Papa, Michaela (Mascot Books, 2018)
In nonfiction, poetry, short fiction, artwork, and detailed interviews, States of the Union collects reflections from everyday Americans on the 2016 presidential election. -Publisher Web Site.
Keywords: 2016; Election; Presidents; United States; dept.eng; faculty_collection